The unbounded home : property values beyond property lines - Fennell, Lee Anne (Yale University Press, 2009)
Lee Anne Fennell explores the relationship between home ownership and neighbourhood, arguing that the desire for active participation in local affairs is directly linked to conern about property values. She looks at how critical issues of neighbourhood control & community composition might be addressed through this link.